2013
DOI: 10.1177/0004865812469973
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the ‘Think First’ program

Abstract: The Think First program was implemented in five NSW correctional centres between 2003 and 2007. This study is a longitudinal evaluation of Think First using the pre- and post-test scores of four questionnaire measures (the Social Problem Solving Inventory – Revised; Barratt Impulsivity Scale, version 11; Locus of Control Behaviour; and the Crime PICS, version II), in a sample of 135 male participants. Significant change in a pro-social direction was found on the Locus of Control Behaviour, all of the Barratt I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…For five, it appeared to be compulsory (Caldwell and Rybroek 2001;Caldwell et al 2006;Forgays and DeMilio 2005;Hoogsteder et al 2018;Strom et al 2017). It is unclear whether the intervention was voluntary or compulsory for the remaining two groups (Bouffard and Bergseth 2008;Hubble et al 2015).…”
Section: Populationmentioning
confidence: 99%
See 4 more Smart Citations
“…For five, it appeared to be compulsory (Caldwell and Rybroek 2001;Caldwell et al 2006;Forgays and DeMilio 2005;Hoogsteder et al 2018;Strom et al 2017). It is unclear whether the intervention was voluntary or compulsory for the remaining two groups (Bouffard and Bergseth 2008;Hubble et al 2015).…”
Section: Populationmentioning
confidence: 99%
“…Of the studies identified, five were based in the community (Bouffard and Bergseth 2008;Burraston et al 2014;Forgays and DeMilio 2005;Haines et al 2015;Hubble et al 2015). However, one of those studies contained youth nearing the end of their custodial sentence before continuing in the community (Bouffard and Bergseth 2008). Participants in seven of the studies resided in custodial placements.…”
Section: Settingsmentioning
confidence: 99%
See 3 more Smart Citations